2005
DOI: 10.1007/s10916-005-6356-1
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Electric Field Effects on Tissues by Using Back Propagation Neural Network

Abstract: The aim of this study is to determine lipid peroxidation and antioxidant enzyme levels in spleen and testis tissues of guinea pigs which were exposed to different intensities and periods of DC (direct current) and AC (alternating current) electric fields. The experimental results are applied to neural networks as learning data and the training of the feed forward neural network is realized. At the end of this training; without applying electric field to the tissues, the determination of the effects of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Four more recent studies on rodents by some of the same investigators who proposed static EF effects on proteins also reported that exposure to static EF can induce oxidative stress in various organs [66, 67, 70, 71]. The authors of these studies did not discuss the potential mechanisms of action by which oxidative stress could be induced and it remains unclear how or why static EF could cause this response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four more recent studies on rodents by some of the same investigators who proposed static EF effects on proteins also reported that exposure to static EF can induce oxidative stress in various organs [66, 67, 70, 71]. The authors of these studies did not discuss the potential mechanisms of action by which oxidative stress could be induced and it remains unclear how or why static EF could cause this response.…”
Section: Resultsmentioning
confidence: 99%
“…Neither were adverse health effects reported upon long-term exposure to a HVDC power line [35]. A great many of the animal studies reported effects on metabolic activity [49, 56, 60, 62, 68], collagen synthesis [59, 63–65], bone density [61], expression of oxidative stress markers [66, 67, 70, 71, 76], hematologic and immunologic blood parameters [4143, 50, 69–72, 74–78], neurotransmitter concentrations [56], brain activity [58], litter number [52], genotoxicity [69, 79], and tumor regression [37]. However, the results regarding these parameters were not always consistent and partially contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall pattern of E field experienced at any point thus depends on the distribution of charges and of objects in the vicinity. For this reason, scientists are curious about the possible effects of the E fields in vertical and horizontal direction particularly on the body weight, mortality and blood protein fraction (Marino et al 1976;1983) beside oxidative stress (Güler et al 2005Harakawa et al 2005) and collagen biosynthesis (Marino and Becker 1970;Ahmadian et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These include antioxidant enzymes like SOD (Osman, 1986; Salo et al , 1990). SOD scavenges the superoxide radicals by catalyzing the reactive species into dioxygen and oxygen peroxide, thereby protecting cells against the reactive oxygen species produced by the electric field or other mechanisms (Güler et al , 1996, 2005). The effects of electric fields on antioxidant enzymes are found by determining the level of SOD in spleen and testis tissues.…”
mentioning
confidence: 99%